STATE DIGITAL SOVEREIGNTY IN THE GOVERNANCE OF ARTIFICIAL INTELLIGENCE WITHIN INDONESIA’S GOVERNMENT SYSTEM - Wiredarme (Ninety Media Publisher, 2023)
This study examines state digital sovereignty in the governance of artificial intelligence within Indonesia’s government system. The main objective is to analyze how the state can maintain effective control over AI infrastructure, public-sector data, and government AI systems while preserving constitutional democracy, citizens’ rights, and public accountability. This research applies a qualitative legal method with normative-juridical, conceptual, and socio-legal approaches. The analysis is based on constitutional principles, statutory regulations, policy documents, and recent scholarly debates on AI governance, digital sovereignty, data sovereignty, and public-sector digital transformation. The findings show that Indonesia has developed important foundations for digital government through the Electronic-Based Government System, One Data Indonesia, the Personal Data Protection Law, and the National Strategy for Artificial Intelligence 2020–2045. Yet these instruments have not fully established a comprehensive framework for sovereign AI governance. The main risks include infrastructure dependency, weak control over public-sector data, vendor dominance, limited algorithmic accountability, and unclear responsibility for AI-based administrative decisions. This study argues that state digital sovereignty in AI governance requires strategic infrastructure control, public-sector data sovereignty, algorithmic accountability, meaningful human authority, and democratic oversight. The contribution of this study lies in framing AI governance not merely as a matter of technological innovation or administrative efficiency, but as a constitutional issue concerning the state’s capacity to govern digital power in the public interest.